Disentangling charge carrier from photothermal effects in plasmonic metal nanostructures - Chao Zhan (Nature Portfolio, 2019)
Confidently separating the photothermal effect from the generation of energetic charge carriers and quantifying their relative contribution to chemical reactions remain a great challenge in plasmon-mediated chemical reactions. Here, authors describe a strategy based on the construction of a plasmonic electrode coupled with photoelectrochemistry to quantitatively disentangle these two effects.